Transient optical absorption technique to test timing properties of LYSO:Ce scintillators for the CMS Barrel Timing Layer. (May 2023) - Tamulaitis, G.; Nargelas, S.; Talochka, Y.; Vaitkevičius, A.; Korjik, M.; Mechinsky, V.; Paramatti, R.; Dafinei, I.; Lucchini, M.T.; Auffray, E.; Kratochwil, N.
Abstract: A novel technique for testing the timing properties of scintillators is presented. The technique is based on transient absorption (TA) induced in a scintillating material by a selective excitation of the activator ion. A figure of merit to assess the timing properties of scintillators is suggested. This parameter was estimated for a set of cerium doped lutetium–yttrium oxyorthosilicate (LYSO:Ce) bars, which have been fabricated for Barrel Timing Layer sensor of Compact Muon Solenoid detector (CMS BTL) and exhibited different timing properties, and compared with the results obtained by conventional coincidence time resolution (CTR) measurements. The figure of merit applied for the tested bars shows a strong correlation (Pearson's correlation coefficient R  = 0.95) with the CTR. These results suggest that the TA technique could be used as an experimental method to expand in a complementary way the extensive qualification procedure of LYSO:Ce crystals that will be performed for the production of the CMS BTL detector. Highligths: Coincidence time resolution correlates with activator population rise time. Population rise time can be probed by transient absorption in femtosecond domain. Transient absorption can be exploited for testing of scintillator timing properties.